Interaction of chlorine with nickel (110) studied by scanning tunnelling microscopy - Fishlock, T; Pethica, J; Jones, F; Egdell, R; Foord, J (1997)
The role of forces in STM image formation has been established from studies on copper and nickel, and the resulting potential for controlled atom movement has generated interest in STM imaging of low coverages of halogens on these surfaces. Here we report atom-resolved images of clean and chlorine-covered nickel (110) surfaces over a range of chlorine coverages. All the images show that chlorine dissociates on the (110) surface into chemisorbed atom pairs oriented along the [001] direction. The atom-atom separation is comparable to the bulk nickel lattice constant. For very low chlorine exposures, strings of chlorine pairs running in the [11̄0] direction are observed, propagating from [001] step edges onto the terraces. High exposures of chlorine produce a number of different co-existing reconstructions, which will be discussed.